The genus Paragymnopleurus shipp, 1897 (Scarabaeidae: Scarabaeinae) in Vietnam - Thu Huong, Nguyen Thi; Khuong, Dang Duc (Academia Journal of Biology, 2014)
In this paper, the key to species of the genus Paragymnopleurus Shipp in Vietnam is provided, including four species and two subspecies; in which, one species is been identified just only to genus. Two species and one subspecies are new records for the fauna of Vietnam.